Treatment of HCV with ABT-450/r–Ombitasvir and Dasabuvir with Ribavirin - Jordan J. Feld; Kris V. Kowdley; Eoin Coakley; Samuel H. Sigal; David R. Nelson; Dorothy H. Crawford; Ola Weiland; Humberto Aguilar; Junyuan Xiong; Edward Tam; Barbara DaSilva-Tillmann; Lois Larsen; et al. (2014)
The interferon-free combination of the protease inhibitor ABT-450 with ritonavir (ABT-450/r) and the NS5A inhibitor ombitasvir (also known as ABT-267) plus the nonnucleoside polymerase inhibitor dasabuvir (also known as ABT-333) and ribavirin has shown efficacy against the hepatitis C virus (HCV) in patients with HCV genotype 1 infection. In this phase 3 trial, we evaluated this regimen in previously untreated patients with HCV genotype 1 infection and no cirrhosis.